2022
DOI: 10.3847/1538-4357/ac6586
|View full text |Cite
|
Sign up to set email alerts
|

Two Rings and a Marginally Resolved, 5 au Disk around LkCa 15 Identified via Near-infrared Sparse Aperture Masking Interferometry

Abstract: Sparse aperture masking interferometry (SAM) is a high-resolution observing technique that allows for imaging at and beyond a telescope’s diffraction limit. The technique is ideal for searching for stellar companions at small separations from their host star; however, previous analyses of SAM observations of young stars surrounded by dusty disks have had difficulties disentangling planet and extended disk emission. We analyze VLT/SPHERE-IRDIS SAM observations of the transition disk LkCa 15, model the extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 63 publications
2
19
1
Order By: Relevance
“…The tentative detection of a companion at ∼6 au using SAM observations of Willson et al (2016) was interpreted using the accreting circumplanetary disk models of Zhu (2015) as a planet and disk with  M M M 10 yr p J 5 2 1 = --, which for an average circumplanetary disk accretion rate sufficient to form a 1 M J planet in 1 Myr of 10 −9 M e yr −1 is equivalent to a planet mass of 10 M J . However, the detected emission may also be from the bright inner disk of DM Tau, as SAM can result in extended emission being confused for point sources (Currie et al 2019;Blakely et al 2022). Overall, the presence of giant planets within the 21 au dust gap of DM Tau is not ruled out at the sensitivity limits of observations to date.…”
Section: Implications For Dust Gap Opening and Presence Of Planetsmentioning
confidence: 87%
See 1 more Smart Citation
“…The tentative detection of a companion at ∼6 au using SAM observations of Willson et al (2016) was interpreted using the accreting circumplanetary disk models of Zhu (2015) as a planet and disk with  M M M 10 yr p J 5 2 1 = --, which for an average circumplanetary disk accretion rate sufficient to form a 1 M J planet in 1 Myr of 10 −9 M e yr −1 is equivalent to a planet mass of 10 M J . However, the detected emission may also be from the bright inner disk of DM Tau, as SAM can result in extended emission being confused for point sources (Currie et al 2019;Blakely et al 2022). Overall, the presence of giant planets within the 21 au dust gap of DM Tau is not ruled out at the sensitivity limits of observations to date.…”
Section: Implications For Dust Gap Opening and Presence Of Planetsmentioning
confidence: 87%
“…Previous searches for planets toward DM Tau have not resulted in a robust detection. A Keck/NIRC2 sparse aperture masking (SAM) search identified a K-band point source at 6 au at 11.0 ± 0.3 mag with 4.27σ significance (Willson et al 2016); however, emission from the inner disk can be spuriously identified as planets in SAM observations (Currie et al 2019;Blakely et al 2022). Uyama et al (2017) observed DM Tau in the Strategic Exploration of Exoplanets and Disks with Subaru (SEEDS) survey with Subaru, and did not detect any companions down to an H-band 5σ contrast limit at 0 25 of 14.76 mag.…”
Section: The Dm Tau Transition Diskmentioning
confidence: 99%
“…10 − 0. 13 (16-21 au; Kraus & Ireland 2012;Sallum et al 2015), which however have been later interpreted as inner disk emission (Thalmann et al 2016;Currie et al 2019;Blakely et al 2022). No CPDs associated to these candidates were detected in 7 mm continuum (Isella et al 2014).…”
Section: Introductionmentioning
confidence: 93%
“…With high-resolution (68 × 47 mas) Atacama Large Millimeter/submillimeter Array (ALMA) observations at 1.3 mm, Facchini et al (2020) showed that the disk has three dust rings exterior to the cavity and suggested that a planet is forming around the bright middle ring. Three giant planet candidates have also been claimed through optical and IR imaging techniques at radial distances of 0 10−0 13 (16-21 au; Kraus & Ireland 2012;Sallum et al 2015), which, however, have been later interpreted as inner disk emission (Thalmann et al 2016;Currie et al 2019;Blakely et al 2022). No CPDs associated with these candidates were detected in 7 mm continuum (Isella et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the use of nested sampling may allow one to reliably calculate the Bayes factor between these two models for such significant detections. For an example of using nested sampling and a Bayes factor to evaluate the presence of an exoplanet from aperture masking interferometry data, see Blakely et al (2022).…”
Section: Detection and Limitsmentioning
confidence: 99%